2008
DOI: 10.1021/ie0715153
|View full text |Cite
|
Sign up to set email alerts
|

Particle Formation in Vinyl Chloride Emulsion Polymerization. Experimental Study

Abstract: Particle formation in vinyl chloride emulsion polymerization has been investigated by means of ab initio and seeded experiments. A series of ab initio polymerizations was run in order to obtain reliable data regarding the dependence of the particle number on the emulsifier (SDS and SDBS) concentration, as well as to analyze the effect of the initiator concentration, stirring rate, and monomer-to-water ratio upon the particle number and the polymerization kinetics. Seeded polymerizations carried out at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…6 We begin by addressing the modeling of particle growth by polymerization and then focus on the more-intricate subjects of particle formation and particle size distribution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6 We begin by addressing the modeling of particle growth by polymerization and then focus on the more-intricate subjects of particle formation and particle size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, to obtain good agreement in runs A21, A20, A17, and A19, the value of fk d given in Table 4 must be multiplied by a factor of 1.5. This change in the kinetics seems to be correlated with the transition observed in the N- [SDS] curve that was identified in the experimental part: 6 the first and the second set of experiments correspond, respectively, to the parts of the curve before and after the sudden increase in particle number. To explain this observation, one could invoke an effect of [SDS] on the rate of initiation and, indeed, the factor of 1.5 is consistent with the dependence of fk d on [SDS] that was measured by Neelsen et al 68 However, note that the latter authors found a continuous increase of fk d with [SDS], whereas our results suggest an abrupt variation of fk d .…”
Section: Comparison Against Experimental Datamentioning
confidence: 88%
See 2 more Smart Citations
“…To obtain diameter sizes below 0.1 lm, it is necessary to use a large amount of surfactant in the polymerization system [1][2][3]. Most experiments regarding emulsion and miniemulsion polymerizations use the surfactants to study the growth mechanism.…”
Section: Introductionmentioning
confidence: 99%